"Human Life is Like a Joke". Ágnes Heller in memoriam. Issue 1 (2nd January 2019) - Czarnecki, Lukasz
ABSTRACT: Ágnes Heller who died on 19 July 2019 was one of the most influential social scientists of the last century, particularly from the publication of Everyday Life Sociology in the 1960s. With analysis of main concepts such as transcendental freedom and hetero interpretation, I wish to pay tribute to my Master of revolutionary ideas in philosophy and sociology in our daily life-world actions. However, Heller's work crossed boundaries between disciplines and include analysis on contemporary literature and music.